Death Ceremony for Pakpak Ethnic Old Man: Semiotic Study - Sinamo, Suriadi (L'Geneus : The Journal Language Generations of Intellectual Society, 2020)
What is discussed in this research is how the stages of the implementation of the Mate Ncayur N Tua ceremony for the Pakpak ethnic group, what are the symbols used in the implementation of the Mate Ncayur N Tua Ceremony for the Pakpak ethnic group and what are the functions and meanings of the symbols used in the Mate Ncayur N Tua ceremony for ethnic groups. Sir. This study uses Peierce's theory (in Hoed, 2011: 46) which states that a sign is something that represents something else, something that can be in the form of experiences, thoughts, feelings, ideas, etc. that can cover life around us. The basic method used in this research is descriptive method starting from the data collection process, to the analysis stage by applying to the subject matter to get a good result.